MINIMALLY INVASIVE SOLUTIONS FOR THE TREATMENT OF WHITE SPOTTS BY FLUOROSE : CLINICAL CASE - Mendes de Lima, Walkiria; Machado de Andrade, Raynara; Roberta Malpeli Gomes, Livia; Auxiliadora Vilela Maia, Elaine; Villas Boas Tavares, Fernanda (Health and Society, 2022)
Objectives: The proposal of this clinical case report was to show the solutions that generate minimal tooth structure wear on treatment of white spots by dental fluorosis, showing the benefits and limitations by suggesting a minimally invasive dentistry. Case report: Patient 28 year old, women, attended in Integrated Dentistry Clinic of the University Center UNIEURO complaining about the aesthetics of her smile, noticed the presence of uniform white spots in the incisal region of the anterior teeth with notorious opacity. The treatment with Dental Whitening started with home bleaching technique for 1 month, then the Icon® system (DMG, Hamburg, Germany) as recommended by the manufacturer. Conclusion: The results were satisfactory, the techniques were excellent for the resolution of the case, there was an improvement in the aesthetics of the smile, also directly enhancing the self-esteem and self-confidence of the patient in their social life, when smiling and talking.